Optimization of fermentation conditions for protein production from effective microorganisms-fermented tiger prawn waste - Zulkeple, Nor Masdiana (2013)
Effective microorganisms or EM have been actively used for various reasons but mainly in the waste water treatment, as plant growth initiators and fertilizers. In this study, fermentations of local tiger prawn waste (Panaeus monodon) by EM were conducted. At the early screening stage, fermentations were carried out at various temperature conditions (25°C, 37°C and 60°C), using various starter inocula (EM/Lactic Acid Bacteria) and different sources of carbon (glucose/brown sugar (BS)). Their pH values, total titratable acidities and lactic acid bacterial growth were examined. The results showed that, all samples were successfully fermented after three days of fermentation process except for fermentation at 60°C. Temperature at 60°C had affected the fermentation considerably where the pH did not rapidly decrease. Various levels of carbon source and inoculum were also investigated during screening. The results showed that, acid production in the fermented sample were dependent on glucose concentration but less dependent on the inoculum level. Based on the screening results, fermentation of prawn waste was carried out using 10% EM inoculum, 10% BS and fermented at 37°C for three days and the produced protein liquor contained 46.67% (w/v), dry weight protein. In the optimization phase using central composite design (CCD), four factors were selected which are temperature (30°C – 50°C), incubation time (3 – 9 days), inoculum size (v/w) (1 - 3%) and carbohydrate level (w/w) (5 - 15%). The processing result was protein content. The results showed that, to obtain high protein content from fermented sample, the most significant factor was the interaction between temperature and % of sugar, and the least was the interaction between % of sugar and % inoculum. High protein content and lower pH value were obtained with the suggested conditions given by the software Design Expert® which are temperature of 30°C, 5% sugar, 1.05% inoculum and incubated for 3 days. After optimization studies, the liquor protein content was increased to 86.35%